Hide & seek - Patterson, James, 1947- (London : HarperCollins, 1997)
Singer/songwriter Maggie Bradford finds herself in the midst of a nightmare when she is accused of murdering her husband, Will Shepard, the world's most glamorous athlete, and the case is complicated by the fact that she has killed before.
Adult.
Adult
Keywords: Soccer players -- Fiction; Stalking -- Fiction; Women singers -- Crimes against -- Fiction; Mystery fiction; Singers -- Fiction; Soccer players -- Fiction; Stalking -- Fiction; Detective and mystery stories